2012
DOI: 10.1016/j.jprot.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Serum profiling of leptospirosis patients to investigate proteomic alterations

Abstract: Leptospirosis is a zoonotic infectious disease of tropical, subtropical and temperate zones, which is caused by the pathogenic spirochetes of genus Leptospira. Although this zoonosis is generally not considered as fatal, the pathogen can eventually cause severe infection with septic shock, multi-organ failure and lethal pulmonary hemorrhages leading to mortality. In this study, we have performed a proteomic analysis of serum samples from leptospirosis patients (n=6), febrile controls (falciparum malaria) (n=8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Moreover, a recent study showed that levels of ApoA-I precursor were reduced up to 3-fold in the sera of human leptospirosis patients (45). All of these findings are consistent with our in vitro results suggesting that binding of ApoA-I to leptospires may be the cause of reduced circulating HDL.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, a recent study showed that levels of ApoA-I precursor were reduced up to 3-fold in the sera of human leptospirosis patients (45). All of these findings are consistent with our in vitro results suggesting that binding of ApoA-I to leptospires may be the cause of reduced circulating HDL.…”
Section: Discussionsupporting
confidence: 93%
“…The tryptic peptides were analyzed with a Q Exactive mass spectrometer (Thermo Fisher Scientific) coupled with a Dionex UltiMate ® 3000 Rapid Separation LC system (Thermo Fisher Scientific 20,21 The UniProt accession database was used to access the 19 overlapping BALF proteins (between Group 1 vs Group 3 and Group 2 vs Group 4) identified in this study. These proteins were uploaded and mapped against the Mus musculus reference dataset to extract and summarize the functional annotation associated with individual genes/proteins or groups of genes/proteins and to identify the gene ontology terms, biological processes, functional classification, and important pathways for each dataset.…”
Section: Mass Spectrometry and Protein Identificationmentioning
confidence: 99%
“…other clinically related illnesses. To this end, in our earlier reports, we have demonstrated that a panel of serum/plasma proteins consisting of six candidates (serum amyloid A, hemopexin, apolipoprotein E, haptoglobin, retinol-binding protein 4 and apolipoprotein A-I) can distinguish malaria from the other infectious diseases with overlapping clinical manifestations (dengue fever and leptospirosis)[13,40,41].…”
mentioning
confidence: 98%